Mobilizing for Jihad: how political exclusion and organized protest contribute to foreign fighter outflows - Fox, Jonathan (Terrorism and political violence, 2024)
This article adds to a growing literature explaining driving forces behind Muslim foreign fighters in Jihadist conflicts. Employing quantitative analyses, we examine counts of Muslim foreign fighters from non-Muslim majority countries in Iraq and Syria from 2011 to 2015. We find that greater numbers of foreign fighters come from countries where Muslim minorities are politically organized, excluded from policymaking processes, and engaged in peaceful mobilization than countries where these conditions are otherwise absent. These results contribute to a more nuanced understanding of the mechanisms by which aggrieved individuals tend to be recruited in larger numbers to participate in foreign wars.